Efecto de la quimioprofilaxis con metotrexate sobre las transaminasas hepáticas en pacientes con mola hidatiforme completa en el hospital Regional Docente de Trujillo, 2002 - 2016 - Vásquez Vereau, Ingrid Raquel (2017)
Determine the effect of chemoprophylaxis with methotrexate on hepatic transaminases in patients with complete hydatidiform mole. Materials and methods: A descriptive, cross-sectional and retrospective study was carried out, which included 95 clinical records of patients with the diagnosis of complete hydatidiform mole who were attended at the Gynecology Service of the Hospital Regional Docente de Trujillo from January 2002 to December 2016 and who received methotrexate. The sample was divided into two groups according to the β-HCG levels ≤ 100 000 UI/ml or > 100 000 UI/ml and the serum levels of the AST and ALT enzymes were recorded before and after the prophylactic administration of methotrexate. Results: Liver transaminases after the methotrexate administration remained within normal ranges in 61.1 % of patients and abnormally elevates in 38.9% of cases. Statistical significance was found (p <0.05) when comparing the variation of transaminases according to the β-HCG levels. Conclusion: Chemoprophylaxis with methotrexate abnormally elevates hepatic transaminases in more than one third of patients with complete hydatidiform mole. As well as abnormally elevates liver transaminases mostly in patients with high risk of malignancy